Coaching clinic research proposal writing: A practical guide to your research success - H. Hardani; Sri Sahbany; Samsul Hadi; Atri Sri Ulandari; Ni Nyoman Ariwidiani; Agus Supinganto (Universitas Muhammadiyah Malang, 2024)
Writing a research proposal is a crucial first step in determining the success of your research project. However, authors often face challenges in formulating proposals that are clear, relevant, and persuasive. The purpose of this service is to help researchers, especially young researchers in making research proposals. The method of implementing this service uses a Coaching Clinic, discussion, and mentoring which is carried out in a hybrid manner with pre-test and post-test. Participants in this Coaching Clinic were young lecturers from Politeknik Medica Farma Husada Mataram and several other universities who participated online. There were 20 participants and it was held online through a Zoom meeting on December 16, 2023. The main target of this activity is young lecturers who have minimal experience writing research proposals. The results of this service show an increase in lecturers' abilities or skills and understanding in writing research proposals by 84.50%. Coaching clinics can improve the ability of lecturers to write research proposals.